Deformation Characteristics of Sand Geofoam Blocks using Large-Scale Oedometer Apparatus - Reza Jamshidi Chenari; Alireza Firoozfar; Shekofeh Attari; Ardavan Izadi; Seyed Ebrahim Shafiei (Salehan Institute of Higher Education, 2017)
As a lightweight fill material, expanded polystyrene (EPS) geofoam block has been successfully utilized in geotechnical applications due to its low density and high compressive strength. Understanding the modulus of elasticity and compressibility coefficient of sand-EPS is an aspect that has not been fully understood which may have a significant effect on the design and construction of geotechnical structures. In this study, an attempt has been made to understand the behavior of deformation characteristic parameters of sand-geofoam block combinations with different patterns, using a newly designed and fabricated large-scale oedometer apparatus. The influence of both different combinations of sand-EPS geofoam and relative densities of soil, on the stress-strain behavior and coefficient of volume compressibility under controlled conditions, are experimentally studied. Specimens of EPS geofoam with a density of 8 kg/m3 were tested in relative densities of 35% and 70% of sand under six different overburden pressures of 50 kPa, 100 kPa, 150 kPa, 200 kPa, 250 kPa, and 300 kPa. From the experimental results, it is observed that the settlement and volume compressibility coefficient substantially increased, as the thickness of EPS geofoam increases. Furthermore, utilization of thinner EPS layers with the constant volume fraction ratio of EPS led to the greater settlement.